Pengembangan Desain Blus dan Rok Zero Waste dengan Konsep Geometric Pattern - Anindhya Riski Fatkharani; Ratna Suhartini (Universitas Negeri Surabaya, 2023)
Zero waste fashion design is product design by implementing a lifestyle to minimize waste by optimizing geometric pattern techniques. The purpose of this study is to describe the results of the development of zero waste blouse and skirt designs with geometric pattern concepts. The research method used is the double diamond design development method which consists of 4 stages, namely (1) discover which is the idea search stage, inspired by the concept of zero waste fashion which has less than 15% waste, (2) define which is identification for taking the source of ideas by creating a moodboard, (3) develop which is developing 4 designs with different placement of batik motifs block system, and (4) deliver, namely 4 design developments that are most in line with zero waste inspiration and geometric pattern techniques. The results of the research data show that to make blouses and skirts, it is necessary to determine the development of designs on the silhouettes of blouses and skirts to match the concept of zero waste with geometric patterns.